The Adaptation of Some Varieties of Rice (Oryza sativa l.) with a Liquid Bioorganic Fertilizer (Pomi) in the Acid Soil - Arvita Netti Sihaloho; Wahyunita Sitinjak; Rosmadelina Purba; Roeskani Sinaga; Meriaty Meriaty (Jurnal Penelitian Pendidikan IPA, 2023)
The aims of the study were to obtain appropriate doses of bioorganic fertilizers (POMI) for the growth and production of several rice varieties and to obtain superior rice varieties that are adaptive to acid soils. The research was conducted in Mariah Bandar Village, Pematang Bandar District. The experimental design used was a Factorial Randomized Block Design (RBD) with two factors and three replications. The first factor was a variety consisting of 3 varieties, namely Inpago 12 Agritan (V1), Galur Nusantara (V2), Inpago Unsoed (V3). The second factor was the dose of bioorganic fertilizer 5 ml, 10 ml and 15 ml/plot with a plot size of 1x 2m. Parameters observed were plant height (cm), number of productive tillers, panicle length (cm), grain weight/clump (g) and grain weight/plot (kg). The results showed that the Inpago Unsoed variety and the Nusantara line were adaptive varieties to acid soils and the application of bioorganic plus fertilizer (Pomi) at a dose of 75 liters/ha or 15 ml/plot